1993
DOI: 10.1055/s-2008-1063519
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Polyp of Posterior Urethra in Children: Report on Seventeen Cases

Abstract: Seventeen cases of a solitary polyp of posterior urethra in children (ages ranged between 4 months and 12 years) are presented. All patients were treated endoscopically using a 10 Fr. pediatric cystoscope, equipped with a straight ahead lens, and a Bugbee 3 Fr. electrode to fulgurate the stalk of the polyp through the urethra, without meatotomy. No complications or relapses are recorded, which proves the safety and the efficiency of the transurethral endoscopic resection in all pediatric ages. With the excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 4 publications
1
29
0
2
Order By: Relevance
“…11 However, cases have also been reported from the second to fourth decades. 6,7,9,12,14,16,17 Their main clinical manifestations are urinary obstruction, urinary hesitancy, dysuria, enuresis, hematuria, infection, and flank pain. They are usually diagnosed by cystourethrography or cystoscopy and are treated by TUR, following which the lesion does not usually recur.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, cases have also been reported from the second to fourth decades. 6,7,9,12,14,16,17 Their main clinical manifestations are urinary obstruction, urinary hesitancy, dysuria, enuresis, hematuria, infection, and flank pain. They are usually diagnosed by cystourethrography or cystoscopy and are treated by TUR, following which the lesion does not usually recur.…”
Section: Discussionmentioning
confidence: 99%
“…Również inne prace wskazują, że głównymi objawami obecności polipa w cewce moczowej, który powoduje utrudnienie odpływu moczu z pęcherza moczowego, są wstrzymywanie moczu, osłabienie strumienia moczu, niepełne opróżnienie pęcherza, zatrzymanie moczu, zakażenia układu moczowego, moczenie, parcia naglące. Ponadto często obserwowanymi objawami są krwinkomocz, który występuje z częstością 30-60% i w około 45% objawy dyzuryczne [6,10]. W prezentowanym przypadku krwiomocz był obserwowany jedynie przejściowo po cewnikowaniu pęcherza moczowego, co mogło wynikać prawdopodobnie z naruszenia delikatnej struktury polipa.…”
Section: Omówienieunclassified
“…Dane z piśmiennictwa wskazują, że u około połowy dzieci z polipami cewki moczowej należy spodziewać się współwy-stępowania innych wad układu moczowego [10]. Najczęściej opisywany jest odpływ pęcherzowo-moczowodowy (VUR; vesico-ureteral reflux), którego obecność również podejrzewano w prezentowanym przypadku -u chłopca występowały nawracające infekcje dróg moczowych, a w USG obserwowano poszerzenia układów kielichowo-miedniczkowych nerek.…”
Section: Omówienieunclassified
“…Castro et al in 1993[5] found 100 published cases in the literature and reported a series of 17 cases. A few other isolated cases have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…De Castro[5] managed 17 cases of posterior urethral polyps endoscopically without complications or relapses. Open surgery should be used only when transurethral resection is not possible.…”
Section: Discussionmentioning
confidence: 99%